Undergraduate experiences of military spouses - Chadwick, Heather L., author; Kuk, Linda, advisor; Doe, Sue, committee member; Mallette, Dawn, committee member; Peila-Shuster, Jackie, committee member (Colorado State University. Libraries, 2018)
The purpose of this interpretive phenomenological analysis was to understand the lived educational experiences of active duty military spouses pursuing an undergraduate degree, with a focus on the perceived opportunities and challenges related to degree completion. Data were collected from nine participants who identified as an active duty military spouse enrolled in an undergraduate program. Three research questions guided this study: What are the educational experiences of active duty military spouses pursuing an undergraduate degree? How do military spouses, as nontraditional students, manage the educational opportunities, benefits, and challenges presented to them while pursuing an undergraduate degree and what success strategies do they use to persevere? How do military spouses view the value and utility of obtaining an undergraduate degree? Data were analyzed and five themes emerged: previous educational experiences before the military, challenges of military life, opportunities of military life, success strategies, and career goals. These students demonstrated a diverse array of expressed motivations and characteristics. The essence of these military spouses was characterized by a form of altruistic resilience. The altruistic or selfless nature of their expressed motives extended beyond their own immediate educational or professional needs and ambitions. Numerous spouses noted the impetus to pursue their education was to inspire their children. Likewise, they often placed the demands of their spouse's military career, and the associated volunteer responsibilities, ahead of their own needs and desires. Yet, they persevered.
Keywords: military spouse; higher education; nontraditional students